The Effect of Service Quality and Container Availability on Export Market Share: Evidence from Fresh Coconut and Natural Rubber Export Services in South Sumatra, Indonesia - Larsen Barasa; Natanael Suranta; April Gunawan Malau; Aditya Rinaldi; Sopia Zahra (Greenation Research & Yayasan Global Resarch National, 2026)
Container shipping logistics is a key determinant of the competitiveness of agricultural commodity exports; however, the mechanism by which service quality at the shipping agent level and container availability jointly determine export market share remains under-examined theoretically, and no empirical research exists on this topic—particularly in the export corridors of developing countries, where no previous studies have modeled these two driving factors simultaneously using causal inference methodology. This study examines the simultaneous effects of service quality (the five dimensions of SERVQUAL) and container availability on the export market share of PT Samudera Agro Logistics (SAL), a shipping agency operating fresh coconut and natural rubber export corridors in South Sumatra, Indonesia. A quantitative cross-sectional design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM), with data collected from 50 operational and managerial decision-makers at 10 active exporting companies, selected through purposive sampling based on direct involvement in SAL’s export service cycle and a minimum of one year of container logistics experience. The results indicate that container availability is the primary driver of export market share (β = 0.557; t = 5.054; p < 0.001), exerting a stronger influence than service quality (β = 0.432; t = 3.502; p < 0.01)—a finding that challenges the dominant view in maritime logistics literature, which focuses on service quality. Together, these two variables explain 57.9% of the variance in export market share (R² = 0.579), with large effect sizes (f² = 0.430 and 0.717) and adequate predictive relevance (Q² = 0.384), confirming the model’s robustness. As its primary theoretical contribution, this study introduces the Logistics Agent Competitiveness Model (LACM), an original framework that integrates SERVQUAL, Resource Based View (RBV), and Service Dominant Logic (SDL), which establishes that container availability is an independent strategic resource, not merely a sub-dimension of service quality, in determining the competitiveness of shipping agents. Practical implications are directed toward shipping agency managers prioritizing container fleet reliability, major shipping companies optimizing feeder allocation strategies, and policymakers addressing structural container imbalances in secondary export corridors.